Banana pest risk assessment along banana trade axes running from low to high altitude sites, in the Eastern DR Congo and in Burundi - Blomme, Guy; Ocimati, Walter; Amato, Serge; Felde, Alexandra zum; Kamira, Muller; Bumba, Mariam; Bahati, Liliane; Amini, Daniel; Ntamwira, Jules Bagula (Academic Journals, 2020)
Pests and diseases greatly contribute to the decline in banana yields, food and income insecurity in the Great Lakes region of Africa. Understanding people’s role in pest and disease spread at landscape level is crucial for effective pest and disease management. To determine this, focus group discussions (FGDs) targeting 10 experienced farmers (50% female and 50% male) were conducted in 27 villages along four banana trade routes in western Burundi and eastern DR Congo. FGDs determined the presence and risk of spread of key banana pests and diseases via the movement of banana bunches, planting material and other products, labourers, traders and farm tools. Black leaf streak (BLS), Fusarium wilt and banana bunchy top disease (BBTD) were reported to have been in the landscape for over 40 years while Xanthomonas wilt (XW) was a more recent introduction (1-7 years). BBTD, XW and weevils were the most prevalent constraints. BBTD was observed at previously unsuitable high-altitude zones, which should be a cause of concern, especially with the current risk of climate change. Climate change, and linked temperature increases, could also worsen the prevalence of XW, weevils, nematodes and BLS. Movement of farming tools by labourers and traders, of planting material/suckers and banana bunches emerged as the most common human practices potentially responsible for the spread and/or build-up of banana pests/diseases. Strengthening farmer’s knowledge and institutional capacities of actors on these different modes of disease spread in banana value chains in the region is recommended.